Direct observation of the ultrafast intersystem crossing in tris(2,2 '-bipyridine) ruthenium(II) using femtosecond stimulated Raman spectroscopy - Yoon, S; Kukura, P; Stuart, C; Mathies, R (2006)
Time-resolved femtosecond stimulated Raman spectroscopy (FSRS) is used to explore the ultrafast intersystem crossing between the metal-to-ligand charge-transfer (MLCT) states of tris(2,2'-bipyridine)ruthenium(II) (). Excitation at 480?nm by a ~35?fs actinic pump pulse initiates electron transfer from the metal to the bipyridine ligands and the subsequent changes in the vibrational structure of the ligands are probed by FSRS with high spectral (10?cm -1 ) and temporal (70?fs) resolution. The unique Raman spectral features of the 3 MLCT state of appear with rise times from 100 to 130?fs. An upper limit for the initial 1 MLCT state lifetime of.